RClone: a package to identify MultiLocus Clonal Lineages and handle clonal data sets in r. Issue 8 (16th March 2016) - Bailleul, Diane; Stoeckel, Solenn; Arnaud‐Haond, Sophie
Summary: Partially, clonal species are common in the Tree of Life. And yet, population genetic models still mostly focus on the extremes: strictly sexual versus purely asexual reproduction. Here, we present an R package built upon genclone software including new functions and several improvements. The RClone package includes functions to handle clonal data sets, allowing (i) checking for data set reliability to discriminate multilocus genotypes (MLGs), (ii) ascertainment of MLG and semi‐automatic determination of clonal lineages (MLL), (iii) genotypic richness and evenness indices calculation based on MLGs or MLLs and (iv) describing several spatial components of clonality. RClone allows the one‐shot analysis of multipopulation data sets without size limitation, suitable for data sets now increasingly produced through next‐generation sequencing. A major improvement compared to existing software is the ability to determine the threshold to cluster similar MLGs into MLLs, based on implemented simulations of sexual events. Several functions allow data importation, conversion and exportation with adegenet, Genetix or Arlequin. RClone is provided with two vignettes to handle analysis on one ( RClone_quickmanual ) or several populations ( RClone_qmsevpops ).